Analisis Keterlambatan Pemberitahuan Pengambilalihan (Akuisisi) Saham PT Karya Prima Agro oleh PT Dharma Setya Nusantara Tbk (Studi Kasus Putusan Nomor : 34/KPPU-M/2020) (International Forum of Researchers and Lecturers, 2023)
Company takeover is a legal act carried out by a legal entity or individual organ to take over company shares. Provisions related to Acquisition are regulated in Law Number 40 of 2007 Concerning Limited Liability Companies, then related to procedures are regulated in Article 29 of Law Number 5 of 1999 in conjunction with Article 5 PP No. 57 of 2010 which requires business actors to notify the KPPU of acquisitions within 30 days after the effective date. This research aims to find out the procedure for acquiring shares of PT Karya Prima Agro Sejahtera by PT Dharma Satya Nusantara Tbk, followed by the obligation to notify the KPPU as well as an analysis of the imposition of sanctions on PT Dharma Satya Nusantara Tbk in Decision 34/KPPU-M/2020. The data in this study were obtained based on primary and secondary data sources. The data collection method in this study was carried out through library research. Based on this research, it can be concluded that the procedure for the acquisition of shares carried out by PT Dharma Satya Nusantara Tbk has not been fully carried out in accordance with the law due to delays in notification of post-acquisition to KPPU for 1,889 (one thousand eight hundred and eighty nine) day. In Decision No 34/KPPU-M/2020 PT PT Dharma Satya Nusantara Tbk was subject to sanctions in the form of fines. The sanctions given are in accordance with the law and the objectives of enforcing business competition law.